Necessidades de Informação e Transferência de Tecnologias dos Produtores Agrários para Adaptação às Mudanças Climáticas no Distrito de Xai -Xai, Província de Gaza - Filimone C; Humulane A; Fabião A; Dimande, B. (IIAM, 2015)
This research was conducted to analyse the problems, knowledge and needs of farming households’ – who are the beneficiaries of the project – in order to propose interventions that meet their needs. The research data collection was based on three strategies, namely: (i) household questionnaires; (ii) focus group discussions with groups of farmers’ association members (iii) semi-structured interviews targeted at community leaders, farmers’ association leaders and extension agents working in the four villages studied. In total 166 households were administered a questionnaire, four focus groups consisting of 04 to 12 people were organized; and 10 key informants were individually interviewed.